The concentration of mercury in organs of Whipfin silver biddy (Gerres filamentosus Cuv.) and Flathead grey mullet (Mugil cephalus L.) in coastal central Vietnam - Thiep Vo Van; Łukasz J. Binkowski; Robert Stawarz (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2018)
The concentration of mercury (Hg) in fish species has direct consequences to health of man and ecosystem. Thus, in this paper, the accumulation of Hg in gills, liver, and muscle of the two fish species (Whipfin silver biddy – Gerres filamentosus and Flathead grey mullet – Mugil cephalus) were measured by cold vapor atomic absorption spectrometry. The fish specimens were collected from local markets and direct fishing with the help of fishermen over the period from July to September 2017 in coastal Vietnam. Differences in the total Hg were found both between two species and organs. The concentration of Hg in all organs investigated of Whipfin silver biddy was higher than of Flathead grey mullet (p < 0.05). The content of Hg in the muscles of Whipfin silver biddy was higher than in liver and gills (p < 0.05), 0.460, 0.245, 0.077 µg g-1 w.w., respectively. Liver of Flathead grey mullet had more Hg accumulated than muscle and gills (0.195, 0.097, 0.046 µg g-1 w.w., respectively). The results revealed that Hg concentrations in Flathead grey mullet did not exceed food fish safety limits established for human consumption while concentration of this toxic element in muscles of Whipin silver biddy almost reached the maximum permissible level.